(untitled) (Journal of the College of Languages (JCL), 2025)
Oktay Rıfat Horozcu is one of the most important poets and literary persona in the modern Turkish literature. Although he focused on the conventions of popular poetry, social traditions, and critical issues, Oktay Rıfat Horozcu also wrote abstract poems that can be called scenarios.Body and spirit represent two important aspects in human life. Human beings enjoy a binary inborn character where the spirit has a great importance like the body and sometimes the spirit has more importance than the body. Both have their needs, problems, and taste. For instance, eating while hungry is a need for the body, love and loveliness represent the need for the spirit. There exist several mental diseases in the same way there exist body diseases. The body and the spirit, which cannot exist without the existence of the other, have been identified, described, and explained repeatedly by several groups in the history of humanity. When it comes to talking about the spirit, poetry has been used to explain the elements that cannot be interpreted. Throughout history, several poets enhanced their poetry by tales of the body and the spirit. One of those poets is undoubtedly Oktay RıfatHorozcu, who is considered to be one of the most important poets in the modern Turkish literature.The paper opens with this detailed abstract. It studies then literary career of Oktay Rıfat Horozcu, the focus would be on his poetic quality. In the next section, the paper focuses on the body and the spirit. Finally, the paper studies tales of the body and the spirit in Oktay Rıfat Horozcu’s poems. ÖZET Oktay Rıfat HOROZCU, 20. yüzyıl Türk Edebiyatının en önemli ve en büyük şairlerinden ve ediplerinden biridir. Halk şiiri geleneği, toplumsal konular ve eleştirel konulara ağırlık veren Oktay Rıfat HOROZCU, giderek soyutlaşan ve senaryo denebilecek uzunlukta şiirler kaleme almıştır.Beden ve ruh, insanın iki yönünü temsil eder. Bu bakıma insan dualist bir yapıda olup, bedeni ne kadar mühimse aynı şekilde ve belki de daha fazla ruhu da önemlidir. Her iki yapının da kendine has ihtiyaçları, sorunları ve zevkleri vardır. Örneğin acıktığında bir şeyler yemek bedenin ihtiyacı iken, sevip sevilmek ruhun ihtiyacıdır. Ne kadar bedensel hastalık varsa bir o kadar ruhi yani psikolojik hastalık mevcuttur. Biri olmadan diğerinin var olması mümkün olmayan beden ve ruh, insanlık tarihi boyunca tanımları yapılmış, tarifleri oluşturulmuş ve pek çok kesim tarafından yüzlerce kez anlatıları yapılmıştır. Bilhassa ruh söz konusu olunca, açıklaması zor ögeleri açıklaması için şiire başvurulmuştur. Tarih içerisinde pek çok şair, hem beden ve hem de ruh anlatıları ile şiirini güçlendirmiştir. İşte bu şairlerden biri de şüphesiz ki 20. Yüzyıl Türk Edebiyatının gördüğü en önemli şairlerden biri olan Oktay Rifat HOROZCU’dur.Çalışmamıza bu kapsamlı özet ile başlıyoruz. Oktay Rıfat HOROZCU’nun edebi yönü ve yapıtları tanıtıldıktan sonra, onun şiir yapısı üzerinde durulacaktır. Ardından beden ve ruh ile ilgili bir bölümden sonra, son olarak Oktay Rıfat HOROZCU’nun şiirlerinde beden ve ruh anlatıları işlenecektir.